2021
DOI: 10.1098/rsif.2020.0970
|View full text |Cite
|
Sign up to set email alerts
|

School closures reduced social mixing of children during COVID-19 with implications for transmission risk and school reopening policies

Abstract: School closures may reduce the size of social networks among children, potentially limiting infectious disease transmission. To estimate the impact of K–12 closures and reopening policies on children's social interactions and COVID-19 incidence in California's Bay Area, we collected data on children's social contacts and assessed implications for transmission using an individual-based model. Elementary and Hispanic children had more contacts during closures than high school and non-Hispanic children, respectiv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 59 publications
0
28
0
1
Order By: Relevance
“…Modeling studies have suggested the potential importance of school-based transmission of SARS-CoV-2. 36 , 37 However, both the World Health Organization and the European Centres for Disease Control synthesized the evidence during 2021 and concluded that, where mitigations are in place, there is limited evidence for rapid transmission of SARS-COV-2 in schools. 38 , 39 Studies in Germany, 40 Norway, 41 Australia, 42 the UK, 43 , 44 and the USA 45 , 46 have all concluded that, with mitigations in place, the overall risk of transmission in schools was limited.…”
Section: Discussionmentioning
confidence: 99%
“…Modeling studies have suggested the potential importance of school-based transmission of SARS-CoV-2. 36 , 37 However, both the World Health Organization and the European Centres for Disease Control synthesized the evidence during 2021 and concluded that, where mitigations are in place, there is limited evidence for rapid transmission of SARS-COV-2 in schools. 38 , 39 Studies in Germany, 40 Norway, 41 Australia, 42 the UK, 43 , 44 and the USA 45 , 46 have all concluded that, with mitigations in place, the overall risk of transmission in schools was limited.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of stay-at-home orders and physical distancing restrictions may differ between communities. For example, while there is some evidence that school closures are associated with reductions in COVID-19 cases at the state level [ 8 ], the relative effectiveness of closures at averting contact across demographic groups is unknown [ 9 , 10 ]. For example, in a sample from the United States, people in neighborhoods within the lowest income quintile reduced days at work by 6.6% following a stay-at-home order, while those in the highest income quintile reduced days at work by 13.7% [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similar results were found by Panovska-Griffiths et al, who used the Covasim individual-based model 32 , and found that a second wave would likely be induced if schools were reopened in the UK alongside various other restriction relaxations 19 . The potential for negative consequences from school reopening have also been supported by similar studies conducted in other countries and settings 30,33,34 , as well as more abstract work assessing generic school settings under assumed mixing patterns 35 . Many of these works also explore possible mitigation measures such as partial school reopening, reducing classes size and increased testing, with most finding that opening earlier years is less dangerous than later years due to their reduced susceptibilities and fewer contacts.…”
Section: Discussionmentioning
confidence: 72%